1999
DOI: 10.1097/00000542-199912000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Alfentanil Causes Less Postoperative Nausea and Vomiting than Equipotent Doses of Fentanyl or Sufentanil in Outpatients 

Abstract: Alfentanil, compared with approximately equipotent doses of fentanyl and sufentanil, is associated with a lower incidence of postoperative nausea and vomiting in outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 24 publications
1
24
1
1
Order By: Relevance
“…Furthermore, different pharmacological traits such as solubility in blood, lean tissue and fat, metabolic transformation and elimination (reduced hepatic metabolism of concomitant medications, amount of fluoride ions), or different effects on stress hormone changes [11], may be responsible for different side effects and complications such as PONV. Whatever the nature of the inhalation anesthetic used, the incidence and severity of PONV are influenced by risk factors such as female gender, nonsmoker status, and history of PONV [12,13]; by the type of surgery [14,15]; and by the opioid and antiemetic drugs used in the perioperative course of anesthesia [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different pharmacological traits such as solubility in blood, lean tissue and fat, metabolic transformation and elimination (reduced hepatic metabolism of concomitant medications, amount of fluoride ions), or different effects on stress hormone changes [11], may be responsible for different side effects and complications such as PONV. Whatever the nature of the inhalation anesthetic used, the incidence and severity of PONV are influenced by risk factors such as female gender, nonsmoker status, and history of PONV [12,13]; by the type of surgery [14,15]; and by the opioid and antiemetic drugs used in the perioperative course of anesthesia [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are congruent with a previous study. [16] The recommended dose for Metoclopramide is 10 mg IV. [9] However, Metoclopramide is not effective in reducing PONV at a 10 mg dosage.…”
Section: Discussionmentioning
confidence: 99%
“…53 Older studies looking for differences between individual non-remifentanil phenylpiperidine derivatives have been contradictory. Brown et al 54 reported no significant differences between alfentanil and fentanyl used intra-operatively for pelvic laparoscopy, whereas Langevin et al 55 reported that the use of alfentanil on induction was associated with less PONV compared with both fentanyl and sufentanil.…”
Section: Referencesmentioning
confidence: 99%